Spending Better to Reduce Stunting in Indonesia : Findings from a Public Expenditure Review - World Bank (World Bank, Washington, DC, 2020)
While Indonesia has successfully decreased early childhood mortality, its stunting rates are among the highest in the world; this has lifelong consequences for health, human capital, poverty, and equity. Indonesia has committed significant resources to improving nutrition outcomes; yet, inequalities in coverage and gaps in quality raises the question whether Indonesia is spending enough on stunting-related interventions and whether it is using its resources efficiently. The main objective of this public expenditure review was to assess the level and allocation of stunting-related expenditures. Findings suggest that overall government spending on nutrition is adequate; instead outcomes may depend more on improving efficiency in the use of resources. Most of the recommendations to improve stunting in Indonesia are cross-cutting issues that will have a much broader impact on the quality of public spending overall. The report is organized into five sections. Section one gives introduction. Section two describes the service delivery environment for nutrition in Indonesia, including the Government of Indonesia’s (GOI’s) nutrition strategy, nutrition delivery platforms, access to nutrition-related services, and the main sources of nutrition-related financing. Section three describes the sources of data and methodology used to identify nutrition related expenditures. Section four presents findings from the central and subnational analysis. Section five summarizes key messages and discusses a set of recommendations to help improve the quality of nutrition-related spending.